Stimulation of Vibrio vulnificus Pyruvate Kinase in the Presence of Glucose to Cope With H2O2 Stress Generated by Its Competitors - Kim, Hey-Min; Yoon, Chang-Kyu; Ham, Hyeong-In; Seok, Yeong-Jae; Park, Young-Ha (Frontiers in Microbiology, 2018)
The bacterial phosphoenolpyruvate (PEP):carbohydrate phosphotransferase system (PTS) regulates a variety of cellular processes in addition to catalyzing the coupled transport and phosphorylation of carbohydrates. We recently reported that, in the presence of glucose, HPr of the PTS is dephosphorylated and interacts with pyruvate kinase A (PykA) catalyzing the conversion of PEP to pyruvate in Vibrio vulnificus. Here, we show that this interaction enables V. vulnificus to survive H2O2 stress by increasing pyruvate production. A pykA deletion mutant was more susceptible to H2O2 stress than wild-type V. vulnificus without any decrease in the expression level of catalase, and this sensitivity was rescued by the addition of pyruvate. The H2O2 sensitivity difference between wild-type and pykA mutant strains becomes more apparent in the presence of glucose. Fungi isolated from the natural habitat of V. vulnificus retarded the growth of the pykA mutant more severely than the wild-type strain in the presence of glucose by glucose oxidase-dependent generation of H2O2. These data suggest that V. vulnificus has evolved to resist the killing action of its fungal competitors by increasing pyruvate production in the presence of glucose.